2006
DOI: 10.1128/jcm.44.5.1630-1634.2006
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Farm Study of Extended-Spectrum β-Lactamase-Mediated Resistance

Abstract: Extended-spectrum ␤-lactamase (ESBL)-mediated resistance is of considerable importance in human medicine. Recently, such enzymes have been reported in bacteria from animals. We describe a longitudinal study of a dairy farm suffering calf scour with high mortality rates. In November 2004, two Escherichia coli isolates with resistance to a wide range of ␤-lactams (including amoxicillin-clavulanate and cefotaxime) were isolated from scouring calves. Testing by PCR and sequence analysis confirmed the isolates as b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
84
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(95 citation statements)
references
References 25 publications
10
84
0
1
Order By: Relevance
“…These plasmids can be considered as "epidemic associated with the emergence of specific ESBL or AmpC gene variants. For instance, the IncA/C plasmids were associated with the emergence of bla CMY-2 in the USA and UK Randall et al, 2011), the IncL/M plasmids were associated to the spread of bla CTX-M-3 in European Eastern countries (Golebiewski et al, 2007), while IncK plasmids carrying bla CTX-M-14 have become diffused in Spain and UK (Cottell et al, 2011;Liebana et al, 2006;Valverde et al, 2009). …”
Section: Plasmidsmentioning
confidence: 99%
“…These plasmids can be considered as "epidemic associated with the emergence of specific ESBL or AmpC gene variants. For instance, the IncA/C plasmids were associated with the emergence of bla CMY-2 in the USA and UK Randall et al, 2011), the IncL/M plasmids were associated to the spread of bla CTX-M-3 in European Eastern countries (Golebiewski et al, 2007), while IncK plasmids carrying bla CTX-M-14 have become diffused in Spain and UK (Cottell et al, 2011;Liebana et al, 2006;Valverde et al, 2009). …”
Section: Plasmidsmentioning
confidence: 99%
“…The majority of the ESBL-producing isolates harboured the bla CTX-M-15 gene, which is carried on plasmids and can be disseminated via horizontal gene transfer to other Gramnegative pathogens (Carattoli, 2009;Liebana et al, 2006). In the current study, a series of ESBL-producing Shigella isolates from South Africa have been identified, which, although comprising ,1 % of all the isolates obtained for surveillance, are clinically relevant as they represent a challenge in disease management and patient treatment.…”
Section: Jmm Correspondencementioning
confidence: 99%
“…ESBL (bla TEM , bla SHV and bla CTX-M ) and AmpC b-lactamase (bla CMY ) genotypes were determined using PCR as described previously (Essack et al, 2001;Liebana et al, 2006;Rankin et al, 2005). Positive controls for PCR included the following strains: Klebsiella pneumoniae ATCC 51503, K. pneumoniae ATCC 700603 and K. pneumoniae D-17.…”
Section: Jmm Correspondencementioning
confidence: 99%
“…CTX-M-type ESBLs have also recently become predominant among ESBLs-positive E. coli [17,18]. Studies from USA, Europe and Asia have shown the recovery of bla CTX-M group from farm livestock with increasing frequency [19][20][21]. The ESBLs-CTX-M type was also reported in faecal samples of broilers [22], and healthy pets [23].…”
Section: Discussionmentioning
confidence: 96%